2016
DOI: 10.1002/jcla.21965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Netrin‐1 Levels and Albuminuria in Patients With Diabetes

Abstract: This study supports that plasma netrin-1 level increases significantly when glomerular damage occurs in diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
4
21
0
Order By: Relevance
“…Liu, et al reported that plasma Netrin‐1 levels were lower in newly diagnosed type 2 diabetes mellitus patients than those in healthy controls and also the levels were negatively correlated with blood glucose levels and insulin resistance. Conversely, increased serum Netrin‐1 concentrations in patients with type 2 diabetes have been reported in recent studies . Our results demonstrated decreased serum Netrin‐1 and Unc5b levels in periodontitis patients and also the levels were negatively correlated with the whole mouth inflammatory clinical parameters.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Liu, et al reported that plasma Netrin‐1 levels were lower in newly diagnosed type 2 diabetes mellitus patients than those in healthy controls and also the levels were negatively correlated with blood glucose levels and insulin resistance. Conversely, increased serum Netrin‐1 concentrations in patients with type 2 diabetes have been reported in recent studies . Our results demonstrated decreased serum Netrin‐1 and Unc5b levels in periodontitis patients and also the levels were negatively correlated with the whole mouth inflammatory clinical parameters.…”
Section: Discussionsupporting
confidence: 66%
“…Conversely, increased serum Netrin-1 concentrations in patients with type 2 diabetes have been reported in recent studies. 32,33 Our results demonstrated decreased serum Netrin-1…”
Section: Discussionmentioning
confidence: 55%
“…Previously, Ay and colleagues reported that serum netrin-1 levels were raised in patients with diabetes whose mean HbA 1c level was 8.1% compared to non-diabetic patients ( 39 ). Also, there was a strong positive correlation between plasma netrin-1 level and HbA 1c , and a significant negative correlation between eGFR, but the study sample was relatively small and a comparative group (such as pre-diabetes) was not included.…”
Section: Discussionmentioning
confidence: 99%
“…Urine netrin-1 concentration has recently received attention as a potential biomarker independently predicting the development of diabetes mellitus and chronic kidney disease. 6,7 In these, a majority of study subjects were those who had already developed chronic renal failure (CRF) with damaged renal function or without diabetes history or just on animal experiments; meanwhile, there were limited data available about the mutual relation between the plasma levels of netrin-1 and inflammation cytokines. The relationship between DN development and plasma netrin-1 levels is unknown.…”
Section: Introductionmentioning
confidence: 99%